If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5a + -4)(3a + 2) = 0 Reorder the terms: (-4 + 5a)(3a + 2) = 0 Reorder the terms: (-4 + 5a)(2 + 3a) = 0 Multiply (-4 + 5a) * (2 + 3a) (-4(2 + 3a) + 5a * (2 + 3a)) = 0 ((2 * -4 + 3a * -4) + 5a * (2 + 3a)) = 0 ((-8 + -12a) + 5a * (2 + 3a)) = 0 (-8 + -12a + (2 * 5a + 3a * 5a)) = 0 (-8 + -12a + (10a + 15a2)) = 0 Combine like terms: -12a + 10a = -2a (-8 + -2a + 15a2) = 0 Solving -8 + -2a + 15a2 = 0 Solving for variable 'a'. Factor a trinomial. (-2 + -3a)(4 + -5a) = 0Subproblem 1
Set the factor '(-2 + -3a)' equal to zero and attempt to solve: Simplifying -2 + -3a = 0 Solving -2 + -3a = 0 Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -3a = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3a = 0 + 2 -3a = 0 + 2 Combine like terms: 0 + 2 = 2 -3a = 2 Divide each side by '-3'. a = -0.6666666667 Simplifying a = -0.6666666667Subproblem 2
Set the factor '(4 + -5a)' equal to zero and attempt to solve: Simplifying 4 + -5a = 0 Solving 4 + -5a = 0 Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -5a = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -5a = 0 + -4 -5a = 0 + -4 Combine like terms: 0 + -4 = -4 -5a = -4 Divide each side by '-5'. a = 0.8 Simplifying a = 0.8Solution
a = {-0.6666666667, 0.8}
| 48=x+y | | 2(8x+64x)=10x+268 | | p-327=415 | | r-191=70 | | 6y=7-4x | | 9r+2=19r+4 | | r-67=164 | | 2-z/2.05=-15 | | 1.5f-5=1 | | m-157=597 | | -3.75y=8 | | 11y=550 | | 2/7(4m-18=12 | | 60+c+90=180 | | 17v=102 | | 8y-7-4y=74-5y | | 7(2x-11)=3(2x-4)+7 | | 13v=559 | | 2(4+3r)-3(r+1)=11 | | (x^2)/(x^2-9) | | 10x^4/5x^3 | | 3x^4=243equation | | 24-30=a | | (W+2)(w+5)=40 | | 2u+2v=10 | | 27=6x^2+1.5x | | -9-3x=14+2x | | 754x=26390 | | 3(a+9)=3(a-5) | | x/1/2=-3/4 | | 265-9= | | 7.52x+4.83(25-x)=158.41 |